Generalized Hermite Spectral Method for Nonlinear Fokker-Planck Equations on the Whole Line (Journal of Mathematical Study, 2018)
In this paper, we develop a spectral method for the nonlinear Fokker-Planckequations modeling the relaxation of fermion and boson gases. A full-discrete generalizedHermite spectral scheme is constructed. Its convergence and stability are provedstrictly. Numerical results show the efficiency of this approach and coincide well withtheoretical analysis.